Resource management and conservation options of Tasek Bera Wetland, Pahang, Malaysia - Rahim @ Abdul Rahim, Hairazi (2018)
Demand factors for a certain environmental asset should be highlighted clearly in determining the most appropriate actions to be taken by resource manager. The main attributes of Tasek Bera wetland currently jeopardized by economic activities and other externalities. Both resource management and conservation options policy should be able to attain a sufficient sum of revenue in order to continuously managing the resources of Tasek Bera wetland efficiently. Hence, this study attempts to estimate the use value of the wetland. Contingent valuation and choice experiment have been used in these exercises. Structured questionnaires have been developed and distributed to the respondents in targeted site of Tasek Bera wetland area specifically at the main entrance. A total of 600 questionnaires have been distributed conveniently among the visitors of Tasek Bera wetland area. However, only 533 respondents were reliably selected for further analyses. Structured questionnaires have been developed and distributed to the respondents in targeted site of Tasek Bera wetland area specifically at the main entrance. Firstly, the study attempted to explore the underlying dimensions that affect the environmental perception among users towards Tasek Bera wetland area. In line with that, the study provided the surface responses and demands by users subject to the needs of efficient resource management and development. The exploratory factor analysis (EFA) has been applied in order to identify the dimensions that affect the environmental perception towards the wetland area. Further then, the study found have confirmed through confirmatory factor analysis (CFA) that visitors’ attitudinal perception towards environmental issues of the wetland has been structured by six factors of wetland function, agricultural activities, efficient management, society benefit, information provided and salient belief. All the factors are interrelated with each other since it has been identified through CFA. In CVM estimation, the reductions of agriculture activities have been found to be significantly raising the utility of respondents towards the wetland. Willingness to pay for the improvement in resource management and conservation options of the wetland has been elicited through the logit model. Approximately 53% of the visitors agreed to pay the hypothetical entrance fee to the wetland area. Dichotomous choice approach has successfully obtained the average hypothetical entrance fee of RM 17.75 per visitor. With a pessimistic scenario consideration, assuming there will only one time donation of the value of entrance fee, the value of contribution to the sustainable management of Tasek Bera wetland has been assumed to be RM 1,538,747.50. Optimistic scenario (monthly basis with annual contribution) on the other hand would give a total value of RM 18,464,970. Two blocks of estimations were analysed which are biodiversity conservation, and ecotourism facilities and services in CE estimation. The concerns of visitors are more towards the restoration of the wetland function of ecosystem for conservation options. A total of 57.22% of them selected one of the options above the status quo level of conservation charge. While in resource management block, visitors mostly preferred in enhancement in license skill tourist guide attribute which recorded 61.16% of respondents selected one of the options above the status quo level of entrance fee. The study estimated the average consumer surplus representing the extra benefits gain from the wetland up to RM 29.86 per individual for the conservation options. Surplus enjoyed by visitors estimated to be RM 39.64 per visitor in the resource management block. The visitor’s preferences identified in the study from the list of attributes level studied would be useful information for resource manager. The study identified that gender, age, education level and work status were significantly influenced the willingness to pay for resource management and conservation options among the visitors of Tasek Bera. Therefore this information would be helpful in deriving the guidelines in efficient improvement of the wetland.